Combined pretreatment strategies to isolate hydrogen generating microflora from Sundarbans mangrove habitat soil and influence of various carbon sources on hydrogen production - Muralikrishnan Veerasamy2, Santanu Das1*, Munmun Sikdar1, Dr. (Journal of Ecobiotechnology, 2012)
Combined pretreatment strategies to isolate hydrogen generating microflora from Sundarbans mangrove habitat soil and influence of various carbon sources on hydrogen production